Examining Contextual Differences in Participant Characteristics and During-Program Occurrences With Drug Court Program Completion. (April 2020) - Shannon, Lisa M.; Jones, Afton Jackson; Newell, Jennifer; Nash, Shondrah; Nichols, Elizabeth
The study purpose was to compare individuals participating in rural and urban drug courts to examine factors associated with program completion. Secondary data (participant assessment; drug court Management Information System) as well as conviction information from a statewide database were examined for a sample of drug court participants ( N = 534). Based on multivariate analysis, for rural participants, two variables were significantly associated with increased program completion: age and outpatient treatment. Conversely, for rural participants, the number of felony/misdemeanor convictions before drug court and receiving an incarceration sanction during drug court were associated with program non-completion. For urban participants, gender and age were associated with increased odds of completion, whereas marital status, education, and past 30-day cocaine use were associated with program non-completion. Findings suggest contextual differences in participant characteristics and during-program occurrences, which ultimately influenced program completion. Understanding contextual factors has important implications for program planning and implementation.